Engineering high charge transfer n-doping of graphene electrodes and its application to organic electronics. Issue 30 (15th July 2015) - Sanders, Simon; Cabrero-Vilatela, Andrea; Kidambi, Piran R.; Alexander-Webber, Jack A.; Weijtens, Christ; Braeuninger-Weimer, Philipp; Aria, Adrianus I.; Qasim, Malik M.; Wilkinson, Timothy D.; Robertson, John; Hofmann, Stephan; Meyer, Jens
Abstract : Using cesium carbonate (Cs2 CO3 ) in an organic matrix, we present a novel strategy for efficient n-doping of monolayer graphene . Abstract : Using thermally evaporated cesium carbonate (Cs2 CO3 ) in an organic matrix, we present a novel strategy for efficient n-doping of monolayer graphene and a ∼90% reduction in its sheet resistance to ∼250 Ohm sq −1 . Photoemission spectroscopy confirms the presence of a large interface dipole of ∼0.9 eV between graphene and the Cs2 CO3 /organic matrix. This leads to a strong charge transfer based doping of graphene with a Fermi level shift of ∼1.0 eV. Using this approach we demonstrate efficient, standard industrial manufacturing process compatible graphene-based inverted organic light emitting diodes on glass and flexible substrates with efficiencies comparable to those of state-of-the-art ITO based devices.